ANALISIS KINERJA PERUSAHAAN DAN ABNORMAL RETURN SAHAM SEBELUM DAN SESUDAH AKUISISI - Hasanah, Ade Nahdiatul; Oktaviani, Trisna Maya (JAK (Jurnal Akuntansi) : Kajian Ilmiah Akuntansi, 2017)
This study aimed to analyze the differences in firm performance and abnormal stock returns before and after the acquisition on corporate acquisitions activity. Corporate performance is measured by using financial ratio: Net Profit Margin (NPM), Erning Per Share (EPS), Total Asset Trun Oven (TATO), Current Ratio (CR) and Debt Ratio.Quantitative method is used in this research, take the data of public company which had conducted mergers and acquisitions in Indonesia Stock Exchange (IDX) and announce its activity in the period 2013. Sampling method applied in this reaserch is purposive sampling, while there are nine acquirer companies entering in research criterion. Data analysis method data normality, difference test Paired Sample T-Test analysis Market Adjusted Mode).The results of the testing of the hypothesis shows that there are significant differences in the ratio erning per share (EPS) Total Asset Trun Oven (TATO), Net Profit Margin (NPM), and Abnormal Return, but the results of testing against the Debt Ratio and Current Ratio (CR) there significant difference Keywords: Net Profit Margin (NPM), erning per share (EPS), Total Asset Trun Oven (TATO), Debt Ratio and Current Ratio (CR); abnormal Return